Magnetically "Programming" Cobalt-Doped Iron Oxide Nanoparticles for Localized Induction Heating Triggering a Collective Effect of Magnetic Moment Alignment on Demand - Raczka, Theodor (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.